(E)-N-Aryl-2-oxo-2-(3, 4, 5-trimethoxyphenyl)acetohydrazonoyl cyanides as tubulin polymerization inhibitors: Structure-based bioisosterism design, synthesis, biological evaluation, molecular docking and in silico ADME prediction. Issue 20 (1st November 2018) - Wang, Guangcheng; Peng, Zhiyun; Peng, Shanshan; Qiu, Jie; Li, Yongjun; Lan, Yanyu
Graphical abstract: Highlights: ( E )- N -Aryl-2-oxo-2-(3, 4, 5-trimethoxyphenyl)acetohydrazonoyl cyanides were designed and synthesized. In vitro anticancer activities were determined. 3n was most cytotoxic against a panel of cancer cells and multidrug resistant cells. 3n inhibited tubulin polymerization and caused HepG2 cells arrest in G2/M phase. Molecular docking and ADME prediction studies were performed. Abstract: A series of (E)-N-Aryl-2-oxo-2-(3, 4, 5-trimethoxyphenyl)acetohydrazonoyl cyanides have been synthesized and evaluated for their anticancer activity in human hepatocellular liver carcinoma HepG2 and breast adenocarcinoma MCF-7 cell lines. Among all the tested compounds, compound3a, 3e and3n displayed more activity than lead compound with IC50 value of 0.26–0.61 μM. Meanwhile, these compounds (3a, 3e and3n ) showed potent antiproliferative activity against a panel of cancer cells and the HCT-8/T multidrug resistant cell line with IC50 values in the range of 0.077– 7.44 μM. Flow cytometric analyses revealed that compound3n induced cell cycle arrest in G2/M phases in a dose dependent manner. The compound3n also displayed potent tubulin polymerization inhibition with an IC50 value of 0.9 µM, with ten folds more active than colchicine (IC50 = 9 μM). Molecular docking studies revealed that compound3n efficiently interacted with the colchicine binding site of tubulin through hydrophobic, cation-π and hydrogen bond interaction. Furthermore, in silico pharmacokinetic prediction shown that these compounds have a good ADME-related physicochemical parameters. These results demonstrate that3n exhibits potent cytotoxicity in cancer cells by targeting the colchicine binding site of tubulin and potentially acts as a therapeutic lead compound for the development of anticancer drugs.